Short- and long-term periodontal evaluation of impacted canines treated with a closed surgical–orthodontic approach - Aldo Crescini (Blackwell Synergy, 2007)
Aim: The aims were to evaluate and compare the periodontal status of unilateral impacted maxillary canines treated by a combined surgical–orthodontic technique with that of normally erupted controlateral canines. Material and Methods: One hundred and twenty-five patients, consecutively enrolled, aged between 12.8 and 52.0 years, 31 males and 94 females, presented one impacted maxillary canine (test group) and the controlateral canine normally erupted (control group). All cases were treated by a surgical flap and orthodontic traction directed to the centre of the crest and evaluated periodontally at the end of treatment. Fifty-eight patients were followed up for a mean of 3.4 0.5 years. Pocket depth (PD), keratinized tissue width (KT) and gingival recession were recorded. Multilevel models were created. Results: At the end of the orthodontic treatment, PD and KT of the 125 impacted canines were slightly, but statistically significantly higher than controls. Only one treated canine showed a recession (1 mm). At follow-up (58 patients), this difference decreased and the two groups were not significantly different. Conclusions: The combined technique permitted the traction of the impacted canines to the centre of the crest, thus simulating a physiological eruption pattern. Correct alignment and good periodontal status were obtained.